Market-Based Mechanism in Public Service Delivery in Local Government in Poland – A Brief Overview - Sześciło, Dawid (University of Wroclaw. Faculty of Law, Administration & Economics, 2013)
The reintroduction of local self-government at the level of communes (gminy) in 1990 opened the way for an in-depth reform of the local governance framework in Poland. This included not only the legal, organizational and fiscal autonomisation of local communities, but also went in line with general trends concerning the transformation of the public sector. Therefore, among the core elements of the transformation we may identify the extensive privatization of the public service provision schemes. In Poland, this process was not based on the theoretical background of New Public Management, as was the case in a number of Western countries. Instead, it was natural consequence of the rebirth of a market economy with a limited public sector and the intense development of the private market. Those trends were, however, compatible with the NPM programme. The expansion of market-based mechanisms in public service delivery is one of its pillars. This article provides a historical overview of the development of market-based arrangements in public service provision at the most basic level of Polish local government. It is focused mainly on a legal framework, but also includes some observations on the practical side of this process.
Keywords: Polska; samorząd terytorialny; usługi publiczne